2020
DOI: 10.1111/mcn.13120
|View full text |Cite
|
Sign up to set email alerts
|

After their wives have delivered, a lot of men like going out: Perceptions of HIV transmission risk and support for HIV prevention methods during breastfeeding in sub‐Saharan Africa

Abstract: Female-initiated HIV prevention methods, such as oral pre-exposure prophylaxis (PrEP) and the vaginal ring, may be important risk reduction strategies for breastfeeding women. Given their novelty, information about the sociocultural context and how it influences perceptions of and support for their use during breastfeeding is lacking. To address this gap, we conducted 23 focus group discussions separately with pregnant and breastfeeding women, male partners and grandmothers (N = 196) and 36 in-depth interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Participants recognized their differing perspectives related to the timing and implications of sexual practices during pregnancy and postpartum. In previous publications, we found that HCPs are overwhelmingly a trusted source of advice and guidance for women regarding HIV prevention product use [16,21]. In this study we learned that HCPs are also a trusted source when it comes to decision making around sex during pregnancy and while breastfeeding.…”
Section: Discussionmentioning
confidence: 71%
“…Participants recognized their differing perspectives related to the timing and implications of sexual practices during pregnancy and postpartum. In previous publications, we found that HCPs are overwhelmingly a trusted source of advice and guidance for women regarding HIV prevention product use [16,21]. In this study we learned that HCPs are also a trusted source when it comes to decision making around sex during pregnancy and while breastfeeding.…”
Section: Discussionmentioning
confidence: 71%
“…Women's perceived need for HIV protection was often motivated by an STI or concerns about partner non‐monogamy. Motivations regarding partner non‐monogamy may be related to expectations of women in this context to abstain from sex leading up to delivery and/or through 6 months postpartum, a time during which men might be expected to seek other sex partners [ 28 , 29 ]. Though women mostly understood PrEP's function, some incorrectly believed that PrEP could treat or prevent STIs and described this as motivating their PrEP use.…”
Section: Discussionmentioning
confidence: 99%
“…This often led to tension, particularly when other family members were involved. In another study, a lack of support from male partners in sub-Saharan Africa was vividly portrayed by the fact that “male partners tend to seek outside sexual partners during this period because women need time to recover from delivery, women focus their attention on the child, and some men are disgusted by breast milk” [ 40 ]. This finding was slightly different from the findings in our study, though similarly, some fathers left their women alone to pursue other things like work and drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were primiparous or multiparous HIV-positive women of African descent who had given birth at least once in the previous five years after their HIV diagnosis. Purposive sampling was used, though the final sample size was dependent on achieving saturation [ 40 ]. We aimed to achieve maximum variation [ 37 , 41 ] with respect to social class, as well as the length of time since the migration to Canada or the USA in the case of diasporic participants.…”
Section: Methodsmentioning
confidence: 99%